HARMONISASI KEBIJAKAN ADMINISTRASI NEGARA DALAM ERA DESENTRALISASI: TINJAUAN LITERATUR ATAS KONFLIK KEBIJAKAN PUSAT–DAERAH - Muhammad Farisan Kasyfi; Muhammad Gagah Dirgantara (ADMIN: Jurnal Administrasi Negara, 2026)
Abstract Decentralisation is an important strategy in state administrative reform that aims to improve government efficiency, public service quality, and community participation. However, its implementation is often accompanied by policy conflicts between the central and regional governments and between regional governments, which results in policy fragmentation and weakens governance. This study aims to analyse the dynamics of central-regional policy conflicts in the era of decentralisation and examine the role of harmonising state administration policies in realising effective and accountable governance. This study uses a qualitative approach through a literature review of reputable scientific publications indexed by Scopus, with thematic analysis techniques to identify patterns, causal factors, and approaches to policy harmonisation. The results show that policy conflicts are mainly triggered by overlapping regulations, unclear division of authority, differences in political interests, and weak vertical and horizontal coordination mechanisms. Policy harmonisation has proven to play a strategic role in reducing policy conflicts by aligning the objectives, norms, and implementation of policies across levels of government without eliminating the principle of regional autonomy. This study provides a conceptual contribution to strengthening state administration and serves as a basis for developing coherent, effective, and accountable public policies in a decentralised government system